The survey of green lacewings and occurance of Apertochrysa sp. (Neuroptera: Chrysopidae) on various plants in Malaysia. - Alasady, Mohammed Abid Ali; Omar, Dzolkhifli; Ibrahim, Rohani; Ibrahim, Yusof (Academic Journals, 2011)
To determine the species of green lacewings, determine the parasitism of parasite Telenomus sp. on the eggs of Apertochrysa sp. and study the occurrence of Aper-tochrys sp. within the field of corn plants, the experiments were carried out during 2007-2008 in Malaysian agro ecosystem. Collection and direct eggs observation were used in this investigation. Only 18 plants have the eggs of Apertochrysa sp. from 43 surveyed plants. Highest percentage of eggs collected of Apertochrysa sp. 65.84% was collected from citrus trees followed by 26.47% was collected from vegetable plants. The Telenomus sp. was highly affected on the eggs of Apertochrysa sp. and the highest parasitism was re-corded on the eggs which found on corn plant (14%). While, the parasitism was 9.2% on eggs that found in citrus tree. The females of Apertochrysa sp. preferred to lay their eggs on corn plants planted at the east sits of the field. All methods used like handmade white plastic collision trap, sticky traps, knockdown (sondage sampling), shaking, food attractant traps, air blower, spray the adult’s food, color plastic card board traps failed to capture the adults and to sample the immature stages except the eggs directly observation.